Comparative Randomized Study of Balanced Salt Solution and Ringer Lactate Fluid Administration on Plasma Electrolytes, Acid Base Status and Renal Function in Cardiac Surgeries (Global Journal of Medical Research, 2020)
Intra operative fluid therapy is an integral part of anaesthesia management (1). Proper fluid therapy during surgery will avoid hypovolumia and hypotension and maintains proper tissue perfusion and oxygenation. Hypotension avoided by proper diagnosis and treatment of the underlying cause. Important causes of hypotension are blood loss, fluid depletion (intra operative fluid loss plus maintenance), third space losses, evaporative losses from wound, hypoxia and vasodilatory effect of anaesthetic agent. Fluid therapy should not only lead to stablization of macrocirculation, but also of microcirculation. Microcirculation especially seems to be affected by different volume substitution fluid. Physiology and pathophysiology of fluid compartment should be accounted for when decision has to be made among different solution (2). Patient who have to undergo cardiac surgery present a major challenge to the anaesthetist beyond the problem of fluid therapy. In cardiac patient oedema is due to water and salt retention so total body water and sodium is more in these patient but retention of water is more than that of salt so hyponatremia is frequently seen which is dilutional. Remember that hyponatremia is usually dilutional and need fluid restriction. In cardiac patient when diuretics instituted urine output will increase don#x2019;t follow routine guidelines of fluid replacement.